PENERAPAN PENDEKATAN DEEP LEARNING BERBASIS KEARIFAN LOKAL GREBEG SYAWAL UNTUK MELATIH KREATIVITAS MATEMATIS SISWA - Dwi Wulandari, Galuh; Sadieda, Lisanul Uswah; Reny, Riska (Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
The purpose of this study was to determine the effect of mathematics learning using the PBL model with a deep learning approach based on Grebeg Syawal local wisdom on students’ mathematical creativity. The study was conducted in a quasi-experimental framework with a one-group pretest-posttest design. The sample consisted of 36 students of class VIII-E of SMPN 3 Waru Sidoarjo. The instrument used was a test covering four indicators of creativity: fluency, flexibility, originality, and elaboration. The deep learning approach was implemented through three aspects: meaningful learning, mindful learning, and joyful learning. Data analysis was performed using a paired t-test, with data normality tested using the Shapiro-Wilk test. The results showed a significant effect of the Grebeg Syawal local wisdom-based deep learning approach on improving students' mathematical creativity. To increase data validity and obtain a more comprehensive picture of the influence of the Grebeg Syawal local wisdom-based deep learning approach, future research could use an experimental design involving a balanced control and experimental group, or on a broader scale.